2022
DOI: 10.3390/gases2020003
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Assessment in Oil and Gas Construction Projects Using Structural Equation Modeling (PLS-SEM)

Abstract: Oil and gas construction projects are of great importance to support and facilitate the process of operation and production. However, these projects usually face chronic risks that lead to time overrun, cost overrun, and poor quality, affecting the projects’ success. Hence, this study focused on identifying, classifying, and modeling the risk factors that have negative effects on the success of construction projects in Yemen. The data were collected through a structured questionnaire. Statistical analysis, rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 72 publications
1
15
0
1
Order By: Relevance
“…The findings of the correlation and regression analysis indicated that there is a moderate and a significance association of internal risks with the performance of mega constructions projects in Kazakhstan. Thus, the findings are consistent with the studies (Ajibike, et al 2019;Kassem, 2022;) which indicated a significance impact of internal risks factors on oils and gas mga projects. The results from the correlation and regression analysis revealed that there is weak and significance relation of external risks to the performance of mega constructions projects in Kazakhstan.…”
Section: Y (Performance Of Mega Construction Projects) = 1470 +0205 (...supporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the correlation and regression analysis indicated that there is a moderate and a significance association of internal risks with the performance of mega constructions projects in Kazakhstan. Thus, the findings are consistent with the studies (Ajibike, et al 2019;Kassem, 2022;) which indicated a significance impact of internal risks factors on oils and gas mga projects. The results from the correlation and regression analysis revealed that there is weak and significance relation of external risks to the performance of mega constructions projects in Kazakhstan.…”
Section: Y (Performance Of Mega Construction Projects) = 1470 +0205 (...supporting
confidence: 92%
“…Due to these risks, various construction projects were hindered and over budgeted due to mismanagement by the project managers. The community and traditionalbased earning methods, unable to evaluate and handle construction risks, lead to delayed and deficient constructions (Kassem, 2022). Contractual risk is also a major issue in mega projects where contractual allocation risk is one risk factor among the parties involved in the mega project because oil and gas mega-projects involve many parties working on the same project.…”
Section: Risks Influencing Mega Construction Projectsmentioning
confidence: 99%
“…(5) Provide a public and institutional framework for an effective and enhanced current civil engineering standard method of measuring towards creating bills of quantities in the construction sector, and publicly acknowledge and reward the adopters of this approach. (6) The standard has to reflect the most up-to-date technologies in order to align the measuring technique for the future benefit of the building industry.…”
Section: Discussionmentioning
confidence: 99%
“…Tender price uncertainty is reduced or eliminated, and competent contractors may make better-informed decisions because of the standard's emphasis on transparency and objectivity. It does this indirectly by making contract administration easier and decreasing project cost uncertainty [5][6][7]. There is a wealth of research on the tried-and-true approach of measuring adaptation, but there has not been much done to carefully examine this research.…”
Section: Introductionmentioning
confidence: 99%
“…Risk management throughout the project delivery value chain has the potential to help the industry. This may have a cascading impact on a construction project's performance, productivity, budget, and quality [30]. Enshassi and Mosa [31] also said that in order to accomplish a company's goals and expectations, it is important to build a system of time management, cost, safety, and quality to manage a project well.…”
Section: Literature Reviewmentioning
confidence: 99%